Restricted Use Pesticides - Frederick M. Fishel (EDIS)
Restricted use pesticides (RUP) are only for retail sale to, and use by, certified applicators or persons under their direct supervision, and only for those purposes covered by the applicator's certification. When a pesticide is classified as restricted, the label will state "Restricted Use Pesticide" at the top of the front panel. Below this heading may be a statement describing the reason for the restricted classification. There are various reasons which are determined by the U.S. Environmental Protection Agency (EPA) why a particular pesticide is classified as restricted. These criteria involve the EPA's determination that the pesticide may be hazardous to human health or to the environment even when used according to the label. This document is PI-36, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published March 2005.